13C-enrichment NMR spectroscopy: a tool to identify trophic markers and linkages - Bock, Christian; Zhao, Tianyi; Götze, Sandra; Wermter, Felizitas C.; Lannig, Gisela (Frontiers in Marine Science, 2024)
Current climate change, particularly ocean warming, will induce shifts in marine species distribution and composition, affecting the marine food web and, thus, trophic interactions. Analyses of the stable isotopes 13C and 15N are commonly used to detect trophic markers for food web analyses. With the current standard methods used in food web ecology, it is still challenging to identify potential changes in the uptake and utilization of trophic markers. In this work, we present a 13C-enrichment analysis by NMR spectroscopy to track the uptake and utilization of dietary carbon in a simple laboratory experiment of a primary producer and its consumer (algae and bivalve). In particular, we tested the hypothesis of a temperature-dependent use of dietary carbon by tracing the incorporation of 13C-atoms. Unicellular phytoplankton, Phaeodactilum tricornutum, was reared in a medium containing 13C-labeled bicarbonate. The accompanying 13C-NMR spectra of labeled P. tricornutum showed a specific profile of 13C-labeled compounds, including typical trophic markers such as the polyunsaturated omega-3 fatty acid eicosapentaenoic acid (EPA). Afterwards, 13C-labeled P. tricornutum was fed to King scallops, Pecten maximus, kept at two different temperatures (15°C and 20°C). Tissue-specific NMR spectra of P. maximus revealed elevated 13C-NMR signals, particularly of the fatty acid EPA in the digestive gland, which was not evident in muscle tissue. The comparison between the two temperatures indicated a change in trophic markers. At the higher temperature, less unsaturated fatty acids were detected in the digested gland, but increased 13C-labels in sugars were detected in the adductor muscle. This might indicate a change in the uptake and utilization of the trophic marker EPA in P. maximus due to a shift in energy conversion from favored beta-oxidation at colder temperatures to conversion from carbohydrates in the warmth. Our approach indicates that besides the accumulation of trophic markers, their incorporation and conversion are additional important factors for the reliable interpretation of trophic linkages under climate change.